A IMPOSSIBILIDADE DA HISTÓRIA - Sanseverino, Antônio (Organon, 2012)
The historical base of the Brazilian Empire, marked by the Brazilianduality –harmonization between the slavery and the liberalism in the century XIX –,it serves as reference to read the José of Alencar’s romance. It is not a thematicanalysis, but it is an interpretation that evidences in the form, in the type of authoritariannarrator, Alencar’s attempt of to overcome Brazilian tenuousness for the imposedsolution and to invent a national identity.